Effectiveness E-modul based on project-based learning on visual programming courses - Delianti, Putri Irma; Jalinus, Nizwardi (Universitas Negeri Padang, 2020)
This research aimed to analyze the effectiveness of e-modules based on Project Based Learning on Visual Programming. This research uses the Research and Development (R&D) method and the Instructional Development Institute (IDI) model. The research sample were students who were divided into the experimental class and the control class in the Visual Programming. Data analysis was obtained from the results of the posttest and then an analysis was carried out in the form of normality test, homogeneity test and t test. The results of the tests conducted in the control class consisting of 17 students obtained posttest results with an average value of 81.67% and the results of tests conducted in the experimental class consisting of 16 students get the results of the test with an average score of 86 , 54%. Based on prerequisite tests, data analysis, normal, homogeneous experimental research and the use of e-modules this results in significant differences between the control and experimental classes. Based on the results of the posttest and data analysis prerequisite test, it can be concluded that the e-module based on Project Based Learning that is used has been effective.